Algae biogas production focusing on operating conditions and conversion mechanisms – A review - Reham Sayaddi Abusweireh; Natarajan Rajamohan; Christian Sonne; Yasser Vasseghian (Heliyon, 2023)
Global warming is the result of traditional fuel use and manufacturing, which release significant volumes of CO2 and other greenhouse gases from factories. Moreover, rising energy consumption, anticipated limitations of fossil fuels in the near future, and increased interest in renewable energies among scientists, currently increase research in biofuels. In contrast to biomass from urban waste materials or the land, algae have the potential to be a commercially successful aquatic energy crop, offering a greater energy potential. Here we discuss the importance of Anaerobic Digestion (AD) for enhanced biogas yield, characterization, and comparisons between algae pretreatment methods namely, mechanical, thermal, microwave irradiation, and enzymatic and catalytic methods. The importance of anaerobic digestion enhances biogas yield, characterization, and comparisons between mechanical, thermal, microwave irradiation, and enzymatic and catalytic treatment. Additionally, operational aspects such as algal species, temperature, C/N ratio, retention period, and particle size impact biofuel yield. The highest algal biogas yield reported was 740 mL/gVS, subtracted from Taihu de-oiled algae applying thermos-chemical pretreatment under conditions of temperature, time, and catalyst concentration of 70 °C, 3 h, and 6%, respectively. Another high yield of algal-based biogas was obtained from Laminaria sp. with mechanical pretreatment under temperature, time, and VS concentration of 38 ± 1 °C, 15 min, and 2.5% respectively, with a maximum yield of 615 ± 7 mL/g VS. Although biofuels derived from algae species are only partially commercialized, the feedstock for biogas might soon be commercially grown. Algae and other plant species that could be cultivated on marginal lands as affordable energy crops with the potential to contribute to the production of biogas are promising and are already being worked on.